Effect of Ce(III) and Ce(IV) ions on the structure and active protection of PMMA-silica coatings on AA7075 alloy - Trentin, A. [UNESP] (2021)
This work investigates the effect of Ce(III) and Ce(IV) additives on the structure and anti-corrosion properties of poly(methyl methacrylate) (PMMA)-silica coatings on AA7075 aluminium alloy. The results revealed that intermediate Ce(IV) loadings (500 and 1000 ppm) result in a dense hybrid network with a less defective polymeric phase, extending the service time of AA7075 up to 835 days in 3.5% NaCl. Although both additives provide long-term protection, the self-healing ability was observed only for Ce(IV) addition, favoured by the formation of oxides/hydroxides at pH∼3. These properties make the 4 μm-thick PMMA-silica-Ce(IV) coatings very interesting for chromium-free protection technologies.